2011
DOI: 10.2527/jas.2010-3666
|View full text |Cite
|
Sign up to set email alerts
|

NANOG is a key factor for induction of pluripotency in bovine adult fibroblasts1

Abstract: Since the first reports on isolation of pluripotent mouse embryonic stem (ES) cells 3 decades ago, there have been numerous attempts to derive ES cell lines from commercially important livestock species with limited success. The recent discovery that ectopic expression of a handful of stem cell-related genes was capable of inducing pluripotency in rodents and primates provided a novel approach to derivation of pluripotent stem cell lines. We used this approach in cattle and demonstrated that the ectopic expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 22 publications
6
124
0
5
Order By: Relevance
“…Previously, bovine iPSCs have been derived from bovine fetal and adult fibroblasts by retroviral or lentiviral transduction (Cao et al, 2012;Han et al, 2011;Sumer et al, 2011) or nonintegrating plasmids (Huang et al, 2011;Wang et al, 2013). Retroviral and lentiviral vectors are the most commonly used gene delivery systems because they have high transduction rates; lentiviral vectors even allow transduction of nonproliferating cells (Coroadinha et al, 2010;Segura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, bovine iPSCs have been derived from bovine fetal and adult fibroblasts by retroviral or lentiviral transduction (Cao et al, 2012;Han et al, 2011;Sumer et al, 2011) or nonintegrating plasmids (Huang et al, 2011;Wang et al, 2013). Retroviral and lentiviral vectors are the most commonly used gene delivery systems because they have high transduction rates; lentiviral vectors even allow transduction of nonproliferating cells (Coroadinha et al, 2010;Segura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…iPSCs derived from somatic tissue are particularly promising in farm animals in which true, germline-competent embryonic stem cells (ESCs) could not yet be derived (Kumar et al, 2015). Previous approaches to derive bovine iPSCs employed retroviral (Han et al, 2011;Sumer et al, 2011), or lentiviral transduction (Cao et al, 2012) or plasmids (Huang et al, 2011;Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas ES cells are not characterized/ maintained in vitro in farm animals, iPS cells (which are differentiated cells induced to pluripotency with the forced expression of some pluripotency transcription factors, most commonly Oct4, Klf4, Sox2 and c-Myc -OKSM), showed great similarity regarding self-renewing and ability to differentiate into tissues from the three germ layers. Hence, iPS cells are able to maintain the gene expression and typical morphology related to pluripotency even after a long period of in vitro culture (Esteban et al 2009, Nagy et al 2011, Sumer et al 2011.…”
Section: Cloning With Pre-reprogrammed Cells: Induction Into Pluripotmentioning
confidence: 99%
“…Whereas ES cells are not characterized/ maintained in vitro in farm animals, iPS cells (which are differentiated cells induced to pluripotency with the forced expression of some pluripotency transcription factors, most commonly Oct4, Klf4, Sox2 and c-Myc -OKSM), showed great similarity regarding self-renewing and ability to differentiate into tissues from the three germ layers. Hence, iPS cells are able to maintain the gene expression and typical morphology related to pluripotency even after a long period of in vitro culture (Esteban et al 2009, Nagy et al 2011, Sumer et al 2011.Recent data from our research group have shown that cells from farm animals may be reprogrammed to pluripotency after lentiviral transduction of interspecific factors (OKSM), and reprogrammed cells presented several pluripotency markers, being characterized in a pluripotent status not yet seem in stem-cells like from farm animals (Fig.3). Bovine fetal fibroblasts, as well as mesenchymal prior to SCNT is now possible.…”
mentioning
confidence: 99%